Pengaruh Self Efficacy dan Disiplin Belajar Terhadap Perilaku Kecurangan Akademik - Denisa Nopita; Ai Nur Solihat; Kurniawan Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Academic cheating behavior has become normal and common, even though this behavior has serious negative impacts on the perpetrators. So, the importance of conducting this research is to find out what things can influence academic cheating behavior. This research is quantitative research using a survey method with an explanatory design. The population in this study was class XI students at SMA Negeri 8 Tasikmalaya, totaling 404 students. The sampling technique is probability sampling using simple random sampling. Data obtained from distributing questionnaires and analyzed using multiple linear regression tests with the help of the SPSS Version 25 application. The results of the research show 1) There is an influence between self-efficacy on academic cheating behavior with a sig value of 0.000 or <0.005 2) There is a relationship between learning discipline and cheating behavior. student academics with a sig score of 0.000 or <0.005. 3) There is an influence between self-efficacy and learning discipline on academic cheating behavior.